The utilization of exosomes in hydrogels: a bibliometric analysis of publications from 2015 to May 2025 - El Turk, Said; Sajini, Abdulrahim A.; Butt, Haider (Frontiers in Medical Technology, 2025)
This paper is a bibliometric analysis of the utilization of exosomes in hydrogels for various applications, conducted by assessing the relevant documents in this evolving field of research. Since targeted drug delivery, cell communication, and tissue regeneration are of high importance in the field of biomedicine and medical sciences, incorporating exosomes can offer a valuable addition in such applications due to their high bioactivity and biocompatibility. Applications include ocular drug delivery, boosting optic nerve damage, and disease detection, such as cancer and diabetes. Exosome-based technologies have been of interest since the mid-2000s, with an increased momentum in recent years. In this study, data were exported from the Web of Science and Scopus databases and plotted in order to identify the research trends and publication impact in such an evolving area. The analysis reveals that among several countries, China has the greatest number of publications within the period of 2015 to 9th–11th of May 2025, with a contribution of approximately 76.21% and 61.92% based on the WOS and Scopus databases, respectively. Both publications and citation trends show a significant increase with time, reflecting the increased interest in this field. This study aims to provide an overview of the current impact of research on utilizing exosomes in hydrogel systems.